Analisis Efisiensi Penerapan Manajemen Risiko Terhadap Kinerja Keuangan PT Bank Negara Indonesia - Nugroho, Muchammad Rio; Haq, Muhammad Hadyul; Hakim, Yusril Rahman; Ladi Wajuba Perdini Fisabilillah,; Tony Seno Aji, (Independent: Journal of Economics, 2025)
This study aims to analyze the efficiency of risk management implementation on the financial performance of PT Bank Negara Indonesia (Persero) Tbk (BNI) using the Data Envelopment Analysis (DEA) method. The input variables used are Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operating Expenses to Operating Income (BOPO), while the output variables include Return on Assets (ROA) and Return on Equity (ROE). The research findings indicate that perfect technical efficiency (VRSTE = 1.000) was achieved every year during the study period (2019–2023), while full efficiency (CRSTE = 1.000) was only achieved in 2019, 2022, and 2023. In 2020 and 2021, scale efficiency was low, with an average CRSTE over five years of 0.776, indicating that BNI has not fully achieved optimal efficiency in its risk management. The study concludes by emphasizing the need to improve scale efficiency, particularly in certain years, to achieve more optimal financial performance.